Prevalence and risk factors associated with underweight among under-five children in a rural area of Puducherry - Jomon Mathew John; Jomol Sara John (Wolters Kluwer Medknow Publications, 2018)
Background: Nutrition has been recognized as a basic pillar for social and economic development. One in every three malnourished children in the world lives in India. The objective of this study was to measure the prevalence and to study the selected factors associated with underweight among the under-five children in a rural area of Puducherry. Aims: This study aims to study the prevalence of underweight among children under-five years of age and to study the associated risk factors. Methodology: This was a cross-sectional study conducted over a period of 13 months with a sample size of 500. The anthropometric assessments were taken and plotted on the Indian Academy of Pediatrics growth charts.Results: The prevalence of underweight was found to be 23.8%. The age of the child, gender, socioeconomic status, duration of exclusive breast feeds, birth order, and birth weight were found to have statistical significance in underweight. However, the maternal education did not show any significance in underweight. Conclusion: Nutritional status of under-five years children is one of the important indicators of overall development of community and thus country. Intervention to reduce the burden of underweight should be directed toward the education of the mothers regarding the importance of nutrition by community health workers.